Organic residue analysis of two Mississippian period human effigy pipes. (February 2021) - Tolan, Grace; Rebbe, Claire C.; Carmody, Stephen; Blair, Elliot H.; Dye, David H.; Russ, Jon
Highlights: Two effigy pipes from Southeastern North America were analyzed using GC–MS. Two effigy pipes contained nicotine, a biomarker for tobacco. An effigy pipe from Creighton Island off the coast of Georgia (USA) contained carvone. Carvone detected in an effigy pipe indicates spearmint type plant was smoked. Abstract: Organic residue analysis was applied to two Mississippian Period human effigy pipes from the southeastern North America using gas chromatography – mass spectrometry. Both pipes, one recovered from a site in Osceola, Arkansas (USA) and the second from a barrier island near McIntosh County, Georgia (USA), contained trace concentrations of nicotine, indicating the pipes were used to smoke tobacco. The second pipe also contained high concentrations of the monoterpene carvone, the compound that gives spearmint its characteristic aroma. The abundance of carvone along with a mixture of other terpenes and numerous saturated and unsaturated fatty acid methyl esters suggests that an aromatic plant such as spearmint ( Mentha sp.), or possibly a plant extract, was included in the smoking complex.